Effect of Beauregard sweet potato paste supplementation on physicochemical and sensory characteristics of soymilk gelato - Susanti, Siti; Damayanti, Viena Aulia; Legowo, Anang Mohamad; Setiani, Bhakti Etza; Bintoro, Valentinus Priyo; Nuryanto, Nuryanto (Progress in Nutrition, 2025)
Background and aim: Gelato is a frozen dessert that is in demand by many people. Soymilk gelato with the addition of BSP paste is a functional gelato innovation. This study aims to determine effect of variations in BSP paste addition on the physicochemical and hedonic properties of soymilk gelato. Methods: The experimental design used was a CRD with 5 treatments and 4 replications, namely 0%, 7.5%, 15%, 22.5%, and 30% BSP paste. The research method consists of experimental design, research procedures, parameter analysis, and data analysis. Results: The results showed that soymilk gelato with the addition of BSP paste had a significant (p<0.05) effect on the physicochemical and hedonic properties of gelato. The addition of BSP paste increased fiber content, melting resistance, preference for color, taste, and aroma of gelato, as well as decreased fat content, overrun, and preference for texture. Conclusions: The treatment of adding BSP paste as much as 30% was the best treatment.